Factors Influencing the Diagnostic Accuracy of Acoustic Radiation Force Impulse Elastography in Patients with Chronic Hepatitis B - Park, Mi Sung (Gut Liver, 2016)
BACKGROUND/AIMS: To determine factors predictive of discordance in staging liver fibrosis using liver biopsy (LB) and acoustic radiation force impulse (ARFI) elastography in patients with chronic hepatitis B (CHB). METHODS: Consecutive patients with CHB who underwent LB and ARFI elastography on the same day from November 2010 to March 2013 were prospectively recruited from three tertiary hospitals. RESULTS: We analyzed 105 patients (median age of 47 years). The F0–1, F2, F3, and F4 fibrosis stages were identified in 27 (25.7%), 27 (25.7%), 21 (20.0%), and 30 (28.6%) patients, respectively. The areas under the receiver operating characteristics curves for ARFI elastography in assessing ≥F2, ≥F3, and F4 was 0.814, 0.848, and 0.752, respectively. The discordance of at least one stage between LB and ARFI was observed in 68 patients (64.8%) and of at least two stages in 16 patients (15.2%). In a multivariate analysis, advanced fibrosis stage (F3–4) was the only factor that was negatively correlated with one-stage discordance (p=0.042). Moreover, advanced fibrosis stage was negatively (p=0.016) correlated and body mass index (BMI) was positively (p=0.006) correlated with two-stage discordance. CONCLUSIONS: Advanced fibrosis stage (F3–4) was a predictor of nondiscordance between LB and ARFI elastography; BMI also influenced the accuracy of ARFI elastography.